Double-sided effect of tumor microenvironment on platelets targeting nanoparticles. (November 2018) - Chen, Xinli; Wang, Qingbing; Liu, Lisha; Sun, Tao; Zhou, Wenxi; Chen, Qinjun; Lu, Yifei; He, Xi; Zhang, Yu; Zhang, Yujie; Ruan, Chunhui; Guo, Qin; et al.
Abstract: The cancer cells and stromal cells in tumor microenvironment secrete cytokines and recruit "homing" cells (macrophage, lymphocytes, platelets, etc.). Platelets can interact with tumor microenvironment and specifically aggregate at tumor sites. Surprising, we observed different "homing" effects of activated platelets in breast cancer model and pancreatic cancer model which is highly related with the blood supply of tumors. Besides, platelets targeting magnetic nanoparticles (MNPs) can home to breast cancer but be repelled from pancreatic cancer. We observed the targeting effect of MNPs is highly related with the expressions of collagen Ⅰ (marker of extracellular matrix) and CD34 (marker of tumor neovascularization). The homing nanoparticles such as platelets targeting MNPs could realize the tumor targeting ability, photo-thermal effect and tumor immunotherapeutic ability in the accessible tumor (e.g. breast cancer) but not the hypovascular tumor (e.g. pancreatic cancer).